2009
DOI: 10.1002/em.20516
|View full text |Cite
|
Sign up to set email alerts
|

DNA adduct kinetics in reproductive tissues of DNA repair proficient and deficient male mice after oral exposure to benzo(a)pyrene

Abstract: Benzo(a)pyrene (B[a]P) can induce somatic mutations, whereas its potential to induce germ cell mutations is unclear. There is circumstantial evidence that paternal exposure to B[a]P can result in germ cell mutations. Since DNA adducts are thought to be a prerequisite for B[a]P induced mutations, we studied DNA adduct kinetics by 32 P-postlabeling in sperm, testes and lung tissues of male mice after a single exposure to B[a]P (13 mg/kg bw, by gavage). To investigate DNA adduct formation at different stages of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 34 publications
(39 reference statements)
6
25
0
Order By: Relevance
“…This technique also allows the study of small numbers of cells. In contrast, the 32P postlabeling assay is widely used to measure DNA adducts in sperm (9,21,22). That technique detects raw DNA adducts and requires careful interpretation of results if used on ex vivo samples of mixed cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This technique also allows the study of small numbers of cells. In contrast, the 32P postlabeling assay is widely used to measure DNA adducts in sperm (9,21,22). That technique detects raw DNA adducts and requires careful interpretation of results if used on ex vivo samples of mixed cells.…”
Section: Discussionmentioning
confidence: 93%
“…Verhofstad et al (21) recently demonstrated in mice that spermatogonia are particularly sensitive to B[a]P-induced genotoxicity and that nucleotide excision repair is an important factor in maintaining the integrity of the genome. However, the capacity of germ cells to repair DNA damage is lost after meiosis (29).…”
Section: Discussionmentioning
confidence: 98%
“…Changes in the DNA sequence can be induced by exposure to chemicals during life, but may also be inherited via mutations in the spermatogonial stem cells, in that way increasing the risk of developing abnormalities or diseases in the offspring (Vilarino-Guell et al, 2003). B[a]P related DNA damages were observed at all stages of spermatogenesis (Zenzes et al, 1999), which were associated with significantly decreased sperm counts (Verhofstad et al, 2009). …”
Section: Benzo[a]pyrene and Male Fertilitymentioning
confidence: 99%
“…The mutagenic potential of BaP in male germ cells, however, has still not been fully established. BaP-related DNA damage was observed at all stages of spermatogenesis and in testis [44,30], but it is largely unknown how germ cells deal with DNA damage to protect their genetic material, and to prevent the accumulation of mutations in the germ line [30]. However, there are dietary agents which have been found to be beneficial in promoting good health and reducing the carcinogenic risks associated with the exposure to some of these dietary agents [28,25].…”
Section: Introductionmentioning
confidence: 96%
“…The reactive intermediates of BaP metabolism also have the ability to alkylate nucleophilic sites of DNA [18,9], which can lead to the formation of basic sites and DNA strand breaks. Exposure to BaP can lead to structural changes in DNA of somatic cells and as a consequence to increase incidence of somatic diseases with a genetic basis [14,45] and [44]. The mutagenic potential of BaP in male germ cells, however, has still not been fully established.…”
Section: Introductionmentioning
confidence: 96%